Bimbingan Klasikal Berbantuan Multimedia untuk Meningkatkan Pemahaman Diri dalam Perencanaan Karier Siswa - Sabrini, Aliya; Syafriafdi, Non; Oktary, Dian (Universitas Palangka Raya, 2025)
Career planning is an individual process of preparing to choose, design, and determine the career field to pursue. The initial step in career planning is self-understanding. Therefore, students need to be provided with classical guidance to enhance their self-understanding in career planning. The addition of technology-based multimedia is also used to attract students' attention during the guidance process. This study aims to examine the influence of classical guidance assisted by multimedia in improving self-understanding for career planning among students at MAN 2 Kota Pekanbaru. This research employs a quantitative approach using experimental methods. The subjects were selected using purposive sampling, consisting of one class of 36 tenth-grade students with the lowest average scores. The results indicate significant differences before and after the classical guidance intervention, as evidenced by a t-test significance value of 0.000, which is smaller than 0.05. Classical guidance also showed a significant influence, contributing a determinant coefficient of 50.6%. The study concludes that classical guidance assisted by multimedia effectively enhances self-understanding in students' career planning. Future researchers are encouraged to explore other aspects and incorporate more up-to-date media.